2015
DOI: 10.3892/etm.2015.2955
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the herbal formulation Jianpijiedu on the TCRVβCDR3 repertoire in rats with hepatocellular carcinoma and subjected to food restriction combined with laxative

Abstract: The aim of this study was to investigate the effects of the Chinese herbal formulation Jianpijiedu (JPJD) in a rat model of orthotopic hepatocellular carcinoma (OHC). The tumor-bearing rats underwent food restriction combined with laxative (FRL) treatment in order to model the nutritional and digestive symptoms of patients with hepatocellular carcinoma. In addition, the study aimed to elucidate the effect of JPJD on the T cell receptor Vβ-chain complementarity-determining region 3 (TCRVβCDR3) repertoire and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The body odor, mental state, respiration, hair, feces and food-intake were observed and afterwards the SDS scores were recorded based on the SDS Scale listed in Table 1 in order to evaluate the SDS level. According to the previous study (Sun et al, 2016;Shen and Wang, 1987;Zhang et al, 2014;Chen et al, 2014b), the SDS Score below 7 was defined as "Non-SDS", 7-14 as "Mild-SDS", 15-21 as "Typical-SDS" and above 22 as "Severe-SDS".…”
Section: Establishment Of Sds Modelmentioning
confidence: 99%
“…The body odor, mental state, respiration, hair, feces and food-intake were observed and afterwards the SDS scores were recorded based on the SDS Scale listed in Table 1 in order to evaluate the SDS level. According to the previous study (Sun et al, 2016;Shen and Wang, 1987;Zhang et al, 2014;Chen et al, 2014b), the SDS Score below 7 was defined as "Non-SDS", 7-14 as "Mild-SDS", 15-21 as "Typical-SDS" and above 22 as "Severe-SDS".…”
Section: Establishment Of Sds Modelmentioning
confidence: 99%
“…Previous studies have also found that SDS interferes with TME homeostasis in HCC by decreasing the proportion and activity of cytotoxic cells. 5 , 37 Notably, the number of cancer cells was significantly higher in SDS. The SDS-induced immunosuppressive microenvironment avoids the killing of cytotoxic cells 37 ; thus, more cancer cells can be observed under SDS, indicating that SDS promoted HCC progression at the TME level.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, the degree of malignancy was more severe, and the survival time was shorter in HCC rats with SDS, and SDS may accelerate HCC development by interfering with the TME homeostasis and by decreasing the infiltration of cytotoxic cells. 5 , 6 Meanwhile, data from both laboratory and clinical studies tend to support the notion that Chinese herbal medicine can ameliorate the and limit HCC progression by improving the pre-tumorigenic microenvironment. 7 , 8 However, the underlying mechanism by which SDS regulates HCC progression remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…e main components of JJD contain Codonopsis Radix 30 g, Poria 15 g, Atractylodes macrocephala 15 g, licorice 6 g, Bupleurum 12 g, Rhizoma Zedoariae 15 g, and Scutellaria barbata 30 g. Previous studies showed that JJD could improve the food intake of the mice with HCC cachexia effectively, maintain the bodyweight, and prolong the survival time of tumor-bearing mice by regulating the expression of PTEN and FAK [9][10][11]. Clinical studies also showed that JJD could promote the recovery of liver function of HCC patients, improve the postoperative adverse reactions, and improve the quality of life of HCC patients [12].…”
Section: Introductionmentioning
confidence: 99%